2000
DOI: 10.1093/clinchem/46.12.1910
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect between Apolipoprotein E and Angiotensinogen Gene Polymorphisms in the Risk for Early Myocardial Infarction

Abstract: Background: Several studies based on different populations worldwide have described an association between cardiovascular diseases and genetic variations in the apolipoprotein E (APOE), angiotensinogen (AGT), angiotensin receptor type 1 (AT1R), and angiotensin-converting enzyme (ACE) genes. In addition, there is growing evidence of an interaction between hypercholesterolemia and the renin-angiotensin system in the risk for hypertension and atherosclerosis. Methods: To determine whether the DNA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 40 publications
0
10
1
1
Order By: Relevance
“…Based on the search strategy, 571 potentially eligible studies were identified in the initial search. Among these, 22 studies were enrolled in this meta-analysis based on the inclusion criteria [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the search strategy, 571 potentially eligible studies were identified in the initial search. Among these, 22 studies were enrolled in this meta-analysis based on the inclusion criteria [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We conducted systematic reviews of all published studies, abstracts, and letters to the editor, investigating the potential associations between three polymorphisms (ACE D, glycoprotein III PLA2, and F5L) and relevant cardiovascular outcomes. We searched medline (from 1990 to February 2001), and the bibliographies of research reports and meta‐analyses, in order to identify all eligible published studies of PLA2 (13–40), ACE D (8, 41–79), and F5L (80–101). We performed manual searches for additional relevant abstracts from cardiovascular genetic conferences.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, other studies 67,69 did not show any synergistic interactions. Results of a recent study 70 indicate a synergistic effect between AGT M235T and apolipoprotein E4, with increased risk of MI observed in AGT TT and apolipoprotein E4 carriers.…”
Section: Human Genetic Polymorphism Studies Supporting the Role Of Thmentioning
confidence: 96%